Intraperitoneally Administered Vancomycin in Patients with Peritoneal Dialysis-Associated Peritonitis: Population Pharmacokinetics and Dosing Implications - Hartinger, Jan Miroslav; Michaličková, Danica; Dvořáčková, Eliška; Hronová, Karolína; Krekels, Elke H J; Szonowská, Barbora; Bednářová, Vladimíra; Benáková, Hana; Kroneislová, Gabriela; Závora, Jan; Tesař, Vladimír; Slanař, Ondřej (Pharmaceutics, 2023)
Peritonitis is a limiting complication of peritoneal dialysis, which is treated by intraperitoneal administration of antibiotics. Various dosing strategies are recommended for intraperitoneally administered vancomycin, which leads to large differences in intraperitoneal vancomycin exposure. Based on data from therapeutic drug monitoring, we developed the first-ever population pharmacokinetic model for intraperitoneally administered vancomycin to evaluate intraperitoneal and plasma exposure after dosing schedules recommended by the International Society for Peritoneal Dialysis. According to our model, currently recommended dosing schedules lead to possible underdosing of a large proportion of patients. To prevent this, we suggest avoiding intermittent intraperitoneal vancomycin administration, and for the continuous dosing regimen, we suggest a loading dose of 20 mg/kg followed by maintenance doses of 50 mg/L in each dwell to improve the intraperitoneal exposure. Vancomycin plasma level measurement on the fifth day of treatment with subsequent dose adjustment would prevent it from reaching toxic levels in the few patients who are susceptible to overdose.
Keywords: therapeutic drug monitoring; renal replacement therapy; glycopeptides; methicillin resistant Staphylococcus aureus (MRSA); infection; area under the curve (AUC); drug-exposure; continuous ambulatory peritoneal dialysis